The Process of Teaching and Learning of the Reading and Writing of the Mother Tongue (Dulegaya) in Students from the Guna Original People in the Republic of Panama (Global Journal of Human-Social Science, 2022)
This research suggests the analysis and promotion of the mother tongue; "dulegaya" in the bilingual zone, which should start from elementary school, but in practice, the teacher does not promote this language: before, in fact, he contributes without knowing it to its irreparable loss, even in those cases in which, with the best good intention, its revaluation is sought. At the same time, knowledge of the official language is acquired by sacrificing the mother tongue, since the idea that bilingualism should be fought has been internalized in the educational system. Thus, even when the prohibition on the use of dulegaya in the educational environment of Guna Yala is not in force, the teacher is not prepared to accept linguistic-cultural pluralism and will try to achieve cultural homogeneity by curtailing the learning process of the mother tongue. This motivates us to carry out the present investigation. Through it, it is intended to collect the greatest amount of information, in order to summarize what has been investigated to recognize the possible causes of school failure of our dules students (gunas), during the reading and writing learning process; that motivate us to be preventive and make the necessary adjustments during our teaching practice.
Keywords: mother tongue; reading; writing; teaching-learning